EVALUASI PROGRAM RUANG PUBLIK TERPADU RAMAH ANAK DALAM UPAYA PEMENUHAN HAK ANAK DI RPTRA BAMBU PETUNG JAKARTA TIMUR - Tyas Ayu Puspitaningrum; Ida Hayu Dwimawanti; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Child-Friendly Integrated Public Space (RPTRA) in Jakarta is a program created due to the lack of open space for children to play, thus causing children lose their righs. RPTRA Bambu Petung is an RPTRA in East Jakarta that has achieved the highest score in the certification and standardization of Child Friendly Playrooms (RBRA). However, reality shows that the paint on the children's play equipment at RPTRA Bambu Petung contains more than the maximum limit of lead which can be detrimental to children's health. This study aims to identify and analyze the success and inhibiting factors of the implementation of the Bambu Petung RPTRA Program in an effort to fulfill children's rights. The research method used is descriptive qualitative research method. The theory used is the CIPP evaluation theory (Context, Input Process, and Product). The results showed that the implementation of children's activity services in the Bambu Petung RPTRA Program had gone well and succeeded in fulfilling children's rights to play, socialize and recreation, the right to develop children's interests and talents, and the right to education. Even so, several obstacles were still found, namely limited human resources in the form of teaching staff for BKB-PAUD services, budget constraints in the form of no DKI Jakarta APBD allocation for 2021-2022 due to budget refocusing for handling Covid-19 and the absence of effective CSR cooperation. providing monthly financial contributions, as well as limited facilities and infrastructure in the form of parking lots and open stages. The advice given is that it is necessary to increase CSR cooperation between the Bambu Petung RPTRA and private companies, the PPAPP Sub-agency and the Bambu Petung RPTRA Manager carry out official permits for the use of residents' land as a parking facility for RPTRA visitors, and the Facilities and Infrastructure Section of the Bambu Petung RPTRA Management Team in the future must be more careful when receiving game equipment from third parties so that the problem of lead content in the game equipment at RPTRA Bambu Petung does not happen again.